Milkyway image producing Hong Kong film genres for global consumption - Sun, Yi (Springer, 2021)
This book adopts an integrative research framework that primarily combines industrial and discourse analysis to investigate the company Milkyway Image, drawing upon literature that studies film studios and the practices of film production, distribution, and reception. The history of the Hong Kong-based film production company Milkyway Image from its founding in 1996 to the present exemplifies the metamorphosis of the post-return Hong Kong film industry to an era characterised by Hong Kongs integration into a Chinese national context and the transnationalisation of world cinema. It shows that contemporary Hong Kong cinemas transition resists a monolithic chronicle and instead represents a narrative combining the perspectives of different interest groups and a complex process of compliance and resistance, negotiation and contestation. The meaning of Milkyways films shifts as they are circulated across cultures and viewed within diverse frameworks, and our understanding of Hong Kong cinema is subject to varying contexts and historical configurations. For researchers in film and media studies and those who have a general interest in Hong Kong cinema, Asian cinema, or contemporary film culture, this book reveals how a variety of industry and cultural bodies have become co-creators of meaning for a film production house, and how the company operates as a co-creator of the discourse that surrounds it.
Keywords: Milkyway Image; Geschichte 1996-; Filmwirtschaft; Hongkong; Yin he ying xiang (Xianggang) you xian gong si / History; Motion picture studios / China / Hong Kong / History; Motion picture studios; China / Hong Kong; History